After combat : true war stories from Iraq and Afghanistan - Eide, Marian; Gibler, Michael (Potomac Books, An imprint of the University of Nebraska Press, 2018)
"After Combat introduces readers to the wars fought by Millennials from the perspective of the combatants. Told by veterans, After Combat narrates what Tim O'Brien calls a "true war story:" one without obvious purpose or moral imputation, independent of civilian logic, propaganda goals, and even peacetime convention"--